The transformation of the Hong Kong legislative council 1970-1994 from consensus to confrontation. - Miners, Norman (1994)
"Over the past ten years, the Legislative Council has changed from a wholly appointed body subservient to the executive into an obstreperous assembly with an elected majority where government proposals are frequently defeated. This article examines the behaviour of legislators in the period before 1985, during the years 1985 to 1991 when elected members were in a minority and in the most recent period following the 1991 elections. The rules and procedures used by the colonial administration to control the legislature in the past, and the extent to which they still remain effective in limiting its power, are discussed in all other colonies at a similar stage of constitutional development"
Keywords: Hong Kong. Legislative council